The sustainable sites handbook - Calkins, Meg, 1965- (Wiley book on sustainable design., 2011)
"This official reference guide to the Sustainable Sites Initiative Rating System contains information on principles, strategies, technologies, tools, and best practices for sustainable site design applicable to any type of designed landscape, with or without buildings, ranging from shopping malls, streetscapes, subdivisions, corporate and academic campuses, transportation corridors, parks and recreation areas, all the way to single family homes. Equally useful as a guide to achieving SSI credits, or as a guide to independent pursuit of sustainable sites, it offers in-depth coverage on important "green" topics"--